2016
DOI: 10.1007/s40820-016-0100-x
|View full text |Cite
|
Sign up to set email alerts
|

Stable Superwetting Surface Prepared with Tilted Silicon Nanowires

Abstract: Large-scale uniform nanostructured surface with superwettability is crucial in both fundamental research and engineering applications. A facile and controllable approach was employed to fabricate a superwetting tilted silicon nanowires (TSNWs) surface through metal-assisted chemical etching and modification with low-surface-energy material. The contact angle (CA) measurements of the nanostructured surface show a large range from the superhydrophilicity (the CA approximate to 0°) to superhydrophobicity (the CA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The data demonstrated that compared to the Si wafer, the SiNWA tended to better wet. This observation can be explained in terms of the morphology of SiNWA: the nanostructure of the surface increases its contact area with water, which makes the surface more hydrophilic 35 . To investigate the effects of surface chemical properties on the hydrophilic/hydrophobic, we investigated the elements on the surface of SiNWAs by X‐ray photoelectron spectroscopy (XPS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data demonstrated that compared to the Si wafer, the SiNWA tended to better wet. This observation can be explained in terms of the morphology of SiNWA: the nanostructure of the surface increases its contact area with water, which makes the surface more hydrophilic 35 . To investigate the effects of surface chemical properties on the hydrophilic/hydrophobic, we investigated the elements on the surface of SiNWAs by X‐ray photoelectron spectroscopy (XPS).…”
Section: Resultsmentioning
confidence: 99%
“…This observation can be explained in terms of the morphology of SiNWA: the nanostructure of the surface increases its contact area with water, which makes the surface more hydrophilic. 35 To investigate the effects of surface chemical properties on the hydrophilic/hydrophobic, we investigated the elements on the surface of SiN-WAs by X-ray photoelectron spectroscopy (XPS). As shown in Figure 1F, XPS of the silicon peaks revealed the changes at the surface of wafer and SiNWAs.…”
Section: Characterization Of Sinwasmentioning
confidence: 99%
“…Before etching, the silicon wafers were cleaned by toluene, acetone, ethanol, and H 2 O sequentially, followed by immersion in the mixture of H 2 O 2 :H 2 SO 4 (1:3 volume ratios) for 10 min; and then thoroughly rinsed and placed in the deionized water before drying with nitrogen gas. The etching procedure to achieve SiNWs is composed of two steps: in Step 1, the wafers were directly introduced into a mixture of 4.8 M HF and 2, 3, 4, and 8 mM AgNO 3 for 1 min for silver depositing on the surface; in Step 2, the resulting samples were immersed in an etching solution of 4.8 M HF and 0.2 M H 2 O 2 for 30 min, followed by the deionized water rinsing and drying with nitrogen (Meng et al ., 2016). These samples were labeled with the AgNO 3 concentration prepared, e.g.…”
Section: Methodsmentioning
confidence: 99%